Cutaneous manifestation during COVID‐19 pandemic - Galli, Elena (Pediatr Allergy Immunol, 2020)
BACKGROUND: The severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) pandemic, causing COVID‐19, is rapidly spread across the world, by posing novel challenges for all physicians. Cutaneous manifestations of COVID‐19 may be present in 20% of patients, but they are still now poorly characterized. METHODS: We search literature to describe all the various cutaneous manifestation observed during COVID‐19 pandemic. RESULTS: Different cutaneous clinical patterns were described, showing a wide polymorphism. CONCLUSION: We provided an overview of all the various cutaneous manifestations of COVID‐19 described in the literature today, to improve our knowledge and lead a more prompt and accurate diagnosis, especially in asymptomatic or paucisymptomatic cases.